Sacred Groves: As Treasure of Ethnomedicine - Patel, Hetal M.; Adhvaryu, Meghna (Research Advances in Environment, Geography and Earth Science Vol. 6, 2024)
Traditional knowledge of indigenous people should be properly documented as books and PBRs and plant species require conservation and protection before they are obliterated. Biodiversity conservation is a need of a day when deforestation has reached its peak of destruction. Sacred groves (SGs) are specific types of forests where communities' religious and cultural beliefs are used as a tool for in-situ conservation. SGs protect a number of commercially, environmentally, and medicinally significant plant species. Groves are the remnant of virgin forests; it is a belief that they are abode of deities/GODs. It proves a repositories of some endemic, rare and threatened flora. A study was carried out to investigate the ethnobotanical significance of SGs in the Valsad district of Gujarat, India. Primary data collection was done by taking interviews, using questionnaires from ‘Bhagat’ (traditional healer), and local tribes living around these groves. There are 480 SGs documented in the Valsad district, which harbors valuable plant diversity. Among them, 48 SGs were large in size, more than 100 years old, and were selected for ethnobotanical documentation. 182 species have been enumerated as valuable ethnobotanical sp. from these SGs. A total of 76 tree sp. followed by 54 Herbs, 27 climbers and 25 shrubs are identified from the SGs. Plant details such as local name, scientific name, and parts used for ethno medicine in various ailments like jaundice, piles, dysentery, diarrhea, fever, piles, conjunctivitis, ulcers, and kidney stones, etc. were recorded. The most frequently used plant parts were leaves (24%) followed by root (21%), bark (19%), stem (11%), fruits (10%), seeds (6%), flowers (5%) and latex (2%). In District areas, due to high levels of development, anthropogenic activities, modernization and erosion in traditional and civic values (corruption), the conservation of ethnomedicinally important species is affected largely. The existence of SGs and their conservation has made them more diverse; numerous conserved species can be found in large quantities in SGs' native habitats. Before SGs and/or traditional practices are destroyed, traditional knowledge from such conserved places needs to be maintained and should be recorded in books or the People Biodiversity Register (PBR).